Sports Materials - Allen, Thomas (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Advances in materials are crucial to the development of sports equipment, from tennis rackets to skis to running shoes. Materials-driven improvements in equipment have helped athletes perform better, while enhancing safety and making sport more accessible and enjoyable. This book brings together a collection of 10 papers on the topic of sports materials, as published in a Special Issue of Applied Sciences. The papers within this book cover a range of sports, including golf, tennis, table tennis and baseball. State-of-the-art engineering techniques, such as finite element modelling, impact testing and full-field strain measurement, are applied to help further our understanding of sports equipment mechanics and the role of materials, with a view to improving performance, enhancing safety and facilitating informed regulatory decision making. The book also includes papers that describe emerging and novel materials, including auxetic materials with their negative Poisson's ratio (fattening when stretched) and knits made of bamboo charcoal. This collection of papers should serve as a useful resource for sports engineers working in both academia and industry, as well as engineering students who are interested in sports equipment and materials.